Gambaran Tingkat Kemandirian Lansia dengan Rheumatoid Arthritis dalam Pemenuhan Activity Daily Living (ADL) - Savitri, Nurmalita Ayu; Sukmaningtyas, Wilis; Wibowo, Tophan Heri (Publikasi Indonesia, 2022)
Elderly is someone who has entered the age of more than 60 years and over. Arthritis (arthritis) or rheumatism is the number two disease that attacks the elderly in Indonesia. Pain in rheumatoid arthritis patients appears and will cause discomfort and will also be hampered in carrying out various activities. The purpose of this study was to describe the level of independence of the elderly with rheumatoid arthritis in fulfilling daily living (ADL) activities. This research uses descriptive research method. The descriptive method in this study uses a literature review design (Library Study). The search strategy method to find journals used the keywords “Independence OR Independence AND Elderly OR Elderly AND Rheumatoid arthritis OR Rheumatic Disease AND Daily Activity OR Daily Activity OR Activity of Daily Living”. The results of the literature review are known from 7 journals, it can be concluded that 42,8% show that most of the elderly have a level of independence, in the category of moderate dependence, 7 journals show that most of the elderly are >60 years old, 71,4% of journals show that most of the gender of the elderly are women.